Monitoring the photochemistry of a formazan over 15 orders of magnitude in time - Wortmann, Svenja; Kutta, Roger Jan; Nuernberger, Patrick (Frontiers in Chemistry, 2022)
2,3,5-triphenyltetrazolium chloride (TTC) may convert into phenyl-benzo[c]tetrazolocinnolium chloride (PTC) and 1,3,5-triphenylformazan (TPF) under irradiation with light. The latter reaction, albeit enzymatically rather than photochemically, is used in so-called TTC assays indicating cellular respiration and cell growth. In this paper, we address the photochemistry of TPF with time-resolved spectroscopy on various time scales. TPF is stabilized by an intramolecular hydrogen bond and switches photochemically via an E-Z isomerization around an N=N double bond into another TPF-stereoisomer, from which further isomerizations around the C=N double bond of the phenylhydrazone group are possible. We investigate the underlying processes by time-resolved spectroscopy in dependence on excitation wavelength and solvent environment, resolving several intermediates over a temporal range spanning 15 orders of magnitude (hundreds of femtoseconds to hundreds of seconds) along the reaction path. In a quantum-chemical analysis, we identify 16 stable ground-state isomers and discuss which ones are identified in the experimental data. We derive a detailed scheme how these species are thermally and photochemically interconnected and conclude that proton transfer processes are involved.